Influence of Manufacture Process Parameters on Dimensional Stability of Small Blade Castings - Herman, Aleš; Kubelková, Irena; Vrátný, Ondřej; Bednář, Bohumír (Manufacturing Technology Journal, 2019)
The production of precise castings by investment casting becomes an increasingly important manufacturing technology and many of isues of this method have to be addressed. This paper deals with evaluation of critical points on wax patterns of small blades. After the casting of certain product, the casting had a deviation from the required dimension. Investigation revealed that the effect on the resulting dimensional deviation is not only the casting process but also the wax pattern injection process itself. The engine and turbine blades are one of the most important parts in turbine or aircraft engine machinery. Casting deformation is an important feature of evaluation the quality of the turbine blade. In order to control the deformation of the turbine blade during investment casting, a novel compensation method based on reverse deformation was proposed in this study. The article investigates and evaluates critical points for deformation of the blades after their production on wax-press machine. In addition, the effect of the pre-deformation preparation and the human factor influencing effect during assembly is evaluated with the main aspect of not machining all surface of small blades.
Keywords: Investment casting technology; Process stability; Thermography; Blades